Transition Metal-free Photoorganocatalytic Fluoroalkylation Reactions of Organic Compounds - Barata-Vallejo, Sebastián; E. Yerien, Damian; Lantano, Beatriz; Postigo, Al (Current Organic Chemistry, 2016)
The generation of perfluoroalkyl radicals (RF•) by means of photocatalysis is a more suitable route than the established methods employing chemical initiators, like azo or peroxide compounds or the use of transition metals. Conditions governed by photocatalysis can allow for a wide range of functional groups and, therefore, can be applied to the latestage transformation of bioactive molecules. Organic photocatalysts (POC), in the absence of transition metals, can suffer electron-exchange reactions, yielding RF radicals. RF radical production without the assistance of transition metals through the employment of POC will be described, applying this methodology to studying classical examples.
Keywords: fluoroalkyl radicals